Audit Sistem Informasi Pada PT. Alga Rosan Nusantara Menggunakan COBIT 4.1 Domain Ds (Deliver & Support) - Citra Liza Tifania; Brilliant Vergie S; Siti Mukaromah (Journal of Information System and Artificial Intelligence, 2023)
One field that is growing very rapidly is information technology (IT) or information systems (IS). Develop significant exploration and production impacts for each company. All companies want to increase company profits and compete to satisfy whatever consumers want. Information system implementation is carried out to support the process of this business activity. PT also does the same thing. Alga Rosan Nusantara, which has been researching anti-aging degenerative diseases since 2014, is a distributor of traditional online systems (non MLM) that sells healthy anti-aging foods and helps with treatment. The audit was conducted to analyze the awareness of the information integrity of the millet data system used. The audit uses the COBIT 4.1 framework. The domain used is Delivery Service (DS) because this domain is designed with an operational and data management framework. The purpose of this study is to obtain audit results as input data for improving the company's current management system. The results of the study concluded that the information system contained in PT. Alga Rosan Nusantara still has IT governance gap